The Role of Media Quizizz in Civics Learning to Increase Learning Motivation for Elementary School Students - Dwinta, Nita; Sapriya, Sapriya (International Conference on Elementary Education, 2021)
Motivation to learn is one of the attitudes that students must have in the learning process, especially in Civics learning during the COVID-19 pandemic. Lack of motivation to learn in Civics learning during the COVID-19 pandemic was one of the problems during the learning process. Therefore, motivation is needed as a motivating factor for students so that learning is more effective. One of the learning innovations that are suitable for motivating learning during the COVID-19 pandemic and creating an interactive learning process is by using quizizz media. Media quizizz allows students to be actively involved because learning is more fun and challenges students so that it can generate motivation to learn. Through quizizz media, students can improve competence, and teachers can pack learning creatively. The purpose of writing this article is to describe the role of media quizizz in Civics learning towards elementary school student learning motivation. The method used in this research is a literature study that produces a description that media quizzes can arouse student motivation, especially in learning Civics in elementary schools.